Students’ Perception of the Use of “English Phrasal Verb” Videos to Enhance Students’ Independent Learning Skill - Haryanti Haryanti (IJEE (Indonesian Journal of English Education), 2019)
ABSTRACTIndependent English Language Learning is very important to do by students, especially students in higher education level, because they are often required to read many English references and use English on many occasions, for example in writing essays. Also, it is because the opportunity or time to learn English in the class is very limited. Therefore, students badly need to learn English independently outside the classroom. This study was designed to investigate the students’ perception of the use of “English Phrasal Verb” videos in enhancing their independent learning. There were six participants interviewed and observed to get information about the benefits of using “English Phrasal Verb” videos and the effectiveness of it in training the students to be independent learners. The study found that the students’ pronunciation and vocabulary mastery had improved as well as their listening and writing skills due to the use of videos and assignment given. It also revealed that the use of videos had successfully been a trigger for the students to find other English learning videos and learn them independently outside the classroom.ABSTRAKBelajar Bahasa Inggris secara mandiri sangat penting dilakukan oleh siswa, khususnya mahasiswa, karena mereka sering diminta untuk membaca banyak referensi Berbahasa Inggris dan untuk menggunakan Bahasa Inggris di banyak kesempatan, contohnya dalam menulis esai. Selain itu, karena terbatasnya kesempatan atau waktu untuk belajar Bahasa Inggris di kelas, mahasiswa sangat dianjurkan untuk belajar Bahasa Inggris secara mandiri di luar kelas. Penelitian ini didesain untuk menginvestigasi persepsi mahasiswa terhadap penggunaan video tentang frase kata kerja Bahasa Inggris (Phrasal Verbs Videos) dalam meningkatkan kemampuan belajar mandiri mahasiswa. Dalam penelitian ini, terdapat enam peserta yang diwawancarai dan diamati untuk mendapatkan informasi mengenai keuntungan menggunakan video dan keefektifan penggunaan video tersebut dalam melatih mereka menjadi pembelajar mandiri. Penelitian ini menemukan bahwa penguasaan kosakata dan kemampuan pengucapan Bahasa Inggris mahasiswa meningkat begitu juga dengan kemampuan mendengar dan menulis mereka karena penggunaan video yang dimaksud dan tugas yang diberikan. Selain itu, penelitian ini juga menemukan bahwa penggunaan video telah sukses mendorong mahasiswa untuk menemukan video-video belajar Bahasa Inggris lainnya dan untuk mempelajari video-video tersebut secara mandiri di luar kelas. How to Cite: Haryanti. (2019). Students’ Perception of the Use of “English Phrasal Verb” Videos to Enhance Students’ Independent Learning Skill. IJEE (Indonesian Journal of English Education), 6(1), 21-29. doi:10.15408/ijee.v6i1.12613